ini, dan, dari CITA KARA: JURNAL PENCIPTAAN DAN STUDI SENI MURNI: WARNA BIPOLAR SEBAGAI IDE UNTUK MEMBUAT KARYA SENI YANG BAIK - aristi, dewa ayu sakania pradnya; Sujana, I Wayan; Purnami , Ni Made (Program Studi Seni Murni ISI Bali, 2025)
People with bipolar disorder often experience dramatic mood swings, characterized by manic, depressive and mixed symptoms. Drastic emotional changes include feelings of happiness, sadness, fear and other excessive emotions. By using the theory of color psychology, the author wants to visualize facial expressions that come from drastically changing emotional colors. These colors are combined in the opposite way like bipolar traits, resulting in new colors that are visualized in the form of facial expressions